2017
DOI: 10.1002/eqe.2914
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on a new type of earthquake resilient shear wall

Abstract: Summary Reinforced concrete (RC) shear walls have been extensively used as lateral load resisting structural members in tall buildings. However, in the past, strong earthquake events RC structural walls in some buildings suffered severe damage, which concentrated at the bottom and was very difficult to be repaired. The installation of the replaceable corner components (RCCs) at the bottom of the structural wall is a new method to form an earthquake resilient structural wall whose function can be quickly restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…At present, a concept named as resilient city is established to make civil infrastructures enable to be quickly restored after an earthquake [8]. Actually, this resilience indicates that structures could work in a normal/stable working state or a limited elastic-plastic working state during a strong earthquake [9].…”
Section: Introductionmentioning
confidence: 99%
“…At present, a concept named as resilient city is established to make civil infrastructures enable to be quickly restored after an earthquake [8]. Actually, this resilience indicates that structures could work in a normal/stable working state or a limited elastic-plastic working state during a strong earthquake [9].…”
Section: Introductionmentioning
confidence: 99%
“…Replaceable shear wall corner components are another type of replaceable energy dissipation device. Jiang et al proposed a replaceable wall corner component with a mild steel yielding damper, and they showed that shear walls installed with these components could direct the damage to replaceable components, thereby protecting the nonreplaceable areas from damage [31]. Considering the susceptibility of shear wall corners to damage, Lu proposed a new type of shear wall with replaceable corner components by installing replaceable tension-compression bearings at the corners of the shear wall, and these bearings dissipated energy during earthquakes and could be replaced after earthquakes [32].…”
Section: Introductionmentioning
confidence: 99%
“…The ductility of concrete infill is improved through the constraint of steel plates and boundary elements; Zhang et al 3 developed a reinforced concrete (RC) structural wall which is strengthened by X‐shaped prestressed internal braces. The structural wall is self‐centering with reliable energy dissipation capacity because of the embedded braces; Liu et al 4 put forward a new type of ductile shear wall with replaceable corner components, that is, short buckling‐restrained steel braces are installed at the corners of shear walls, which functions to delay concrete crushing and prevent brittle failure.…”
Section: Introductionmentioning
confidence: 99%